PEMANFAATAN MEDIA DIGITAL INERAKTIFE FLAT PANEL DALAM PEMBELAJARAN IPAS MATERI TRADISI DAN BUDAYAKU - Herni Nurhasanah; Siti Mayang Sari; T.M. Haekal (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the use of Interactive Flat Panel digital media in IPAS learning on the topic “Traditions and Culture.” This research employed a qualitative approach with a descriptive method. The research subjects included teachers and students. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing. The results of the study indicate that the use of Interactive Flat Panel media is able to create a more interactive, engaging, and contextual learning environment. Teachers can present materials on traditions and culture through visual displays, videos, and interactive activities that enhance student participation. Students appear more active in asking questions, participating in discussions, and demonstrating a better understanding of cultural diversity in their surroundings. In conclusion, the use of Interactive Flat Panel digital media in IPAS learning contributes positively to improving the quality of learning, particularly on the topic “Traditions and Culture.” Therefore, the use of interactive digital media is recommended to be continuously developed as an innovation in elementary school learning.